Dampak Dari Struktur Aktiva, Firm size, Pertumbuhan Perusahaan Terhadap Struktur Modal Pada Perusahaan Manufaktur - Sry Yulia Anrizal; Ash Shadiq Egim; Gea Ramadhani (Universitas Negeri Padang, 2023)
The main objective of this research is to examine the effect of asset structure, company size and company growth on capital structure. Seventy-nine (79) companies were selected using the purposive sampling method from companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This study used multiple regression analysis to analyze the data and used SPSS 21 to process the data. The main results are: 1). Asset structure variable (X1) has no impact on capital structure and has a negative relationship, 2). Firm size variable (X2) has an impact on capital structure and a positive relationship, 3). The company growth variable (X3) has no impact on capital structure and has a negative relationship. Based on the results of the F test, it is known that simultaneously the independent variables consisting of asset structure, company size and company growth have no effect on capital structure simultaneously (simultaneously). Based on the results of the Determination Coefficient Test (R2) it is known that capital structure (Y) can be explained by three independent variables, namely asset structure (X1), firm size (X2) and company growth (X3) of 1.3%. While the remaining 98.7% can be explained by other variables not included in this research model.